2018
DOI: 10.1002/mabi.201700363
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gastrointestinal Delivery of Nutraceuticals with Polysaccharide‐Based Coatings

Abstract: Oral delivery is one of the facile methods for the administration of active ingredients (AIs) like nutraceuticals and drugs. However, its intrinsic disadvantages include poor absorption and bioavailability, degradation of the AI during transit through the gastrointestinal tract (GIT), and a lack of action specificity. Hence, a delivery system for targeted gastrointestinal delivery of AI using polysaccharide-based polymers, that are generally recognized as safe and approved for use as a direct food additive, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Polysaccharides that have various enzymatic susceptibilities to ensure specific degradation in the small or large intestine when used as a NP coating can efficiently retard the nonspecific release of encapsulated bioactive compounds until the coating is exposed to its intended environment of release, and such coated NPs can be potentially targeted to different GI tract organs and taken up by the enterocytes, providing improved oral bioavailability [89].…”
Section: Types Of Formulations and Used Materialsmentioning
confidence: 99%
“…Polysaccharides that have various enzymatic susceptibilities to ensure specific degradation in the small or large intestine when used as a NP coating can efficiently retard the nonspecific release of encapsulated bioactive compounds until the coating is exposed to its intended environment of release, and such coated NPs can be potentially targeted to different GI tract organs and taken up by the enterocytes, providing improved oral bioavailability [89].…”
Section: Types Of Formulations and Used Materialsmentioning
confidence: 99%
“…The chnp were designed in a way to be taken up by the enterocytes lining the small intestine to increase the bioavailability of the encapsulated compound. Having previously shown the uptake of chnp by Caco2 cells, 23 the release kinetics study evaluated the ability of the particles to release P4 inside the lysosome of the cells during the cell uptake. This was simulated using the pH 4.4 medium to mimic the condition inside the lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…The fabrication and characterization of chitosan nanoparticles (chnp) and chnp coated with starch (C+S) were conducted similar to what had previously been reported by the authors. 23 Briefly, chnp were fabricated using electrospraying with the optimized parameters as follows: the concentration of chitosan dissolved in 50% acetic acid, 0.1% W/V; the concentration of TPP dissolved in water, 1% W/V with 0.5% (V/V) Tween 80; voltage, 25 kV; flow rate, 0.2 mL h –1 ; and working distance, 7 cm. The particles were electrosprayed directly into the cross-linking TPP solution and collected by centrifugation at an RCF of 13 000 g .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles based on hydroxypropyl-β-CD and chitosan can be used in targeting various organs of the gastrointestinal tract. A study of the release of hydrophobic substrate from this composition showed a sharp release (more than 40%) in the gastric fluid due to the breakdown of chitosan and β-CD inclusion complex at low pH [ 261 ]. As in the case of hydrophilic substrate, only a small amount of hydrophobic substrate is released in the intestinal fluid.…”
Section: Mucoadhesive Properties Of Supramolecular Systems Based Omentioning
confidence: 99%